Borders that Divide: Education and Religion in Ghana and Togo since Colonial Times - Denis Cogneau; Alexander Moradi (African Economic History Network (AEHN), 2013)
The partition of German Togoland after WWI provides a natural experiment allowing to test what impact colonial policies really had. Using a data set of recruits to the Ghana colonial army 1908-1955, we find literacy and religious beliefs to diverge at the border between British and French mandated part of Togoland as early as in the 1920s. We attribute this to the different policies towards missionary schools. The divergence is only visible in the South where educational and evangelization efforts were strong enough. Using contemporary survey data we find that border effects originated at colonial times still persist today.
Keywords: N37; N97; 330; Africa; German Togoland; colonial policies; missionary schools